The specifics and complexity of EU public diplomacy - Saliu, Hasan (Družboslovne razprave, 2021)
The European Union (EU) is responsible for important public diplomacy programmes, including Erasmus+. Most European countries engage in activities to enhance their international image parallel to the efforts of the EU itself. By comparing the public diplomacy activities of the USA, as the founder of public diplomacy, and those of the EU, this paper aims to identify the EU's distinctive features in its image-enhancing endeavours. The paper concludes that the EU and the USA often show that they hold different values, ones that make them more attractive to foreign publics. The paper also notes the soft power held by EU member states continues to be much stronger than the effects of the EU's public diplomacy activities in boosting their image.
Keywords: Evropska unija; international image; javna diplomacija; mednarodna podoba; mehka moč; Odnosi z javnostmi; public diplomacy; Public relations; soft power